2017
DOI: 10.1167/iovs.17-21863
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Functional and Structural Evaluation Reveals Neuroretinal Impairment in Early Diabetic Retinopathy

Abstract: PurposeTo test whether quantitative functional tests and optical coherence tomography (OCT)-defined structure can serve as effective tools to diagnose and monitor early diabetic neuroretinal disease.MethodsFifty-seven subjects with diabetes (23 without diabetic retinopathy [no DR], 19 with mild nonproliferative diabetic retinopathy [mild NPDR], 15 with moderate to severe [moderate NPDR]), and 18 controls underwent full ophthalmic examination, fundus photography, spectral-domain optical coherence tomography (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 73 publications
(124 reference statements)
7
80
2
2
Order By: Relevance
“…; Joltikov et al. ). The minimum contrast threshold of the 5° diameter stimulus was measured at each of 55 test locations (Joltikov et al.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Joltikov et al. ). The minimum contrast threshold of the 5° diameter stimulus was measured at each of 55 test locations (Joltikov et al.…”
Section: Methodsmentioning
confidence: 97%
“…The minimum contrast threshold of the 5° diameter stimulus was measured at each of 55 test locations (Joltikov et al. ). The testing time was approximately 5 min per eye.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, besides VA tests, some experts suggested that psychophysical tests, such as visual field and contrast sensitivity test, should also be evaluated in DR patients with optic nerve complication. They found that those examinations were more sensitive than VA test only [13].…”
Section: Visual Acuitymentioning
confidence: 98%
“…Chronic hyperglycemia damages the retinal blood vessels and causes pericyte loss due to elevated sorbitol level. These result in involution of the vascular changes in microcirculation and loss of normal capillary exchange [12][13][14]. Microvascular anomalies and chronic inflammation may develop dysfunctional barriers permitting leakage of inflammatory molecules and immune cells from systemic circulation and cause further deterioration of the tissue [12,41].…”
Section: Hemodynamic Changesmentioning
confidence: 99%
See 1 more Smart Citation